Guidelines, the Internet, and Personal Health - Moehr, J. R. (Methods of Information in Medicine, 2002)
Objectives: To summarize the insights gained in collaborative research in a Canadian Network of Centres of Excellence, devoted to the promotion of evidence-based practice, and to relate this experience to Internet support of health promotion and consumer health informatics.Methods: A subjective review of insights is undertaken.Results: Work directed the development of systems incorporating guidelines, care maps, etc., for use by professionals met with limited acceptance. Evidence-based tools for health care consumers are a desirable complement but require radically different content and delivery modes. In addition to evidence-based material offered by professionals, a wide array of Internet-based products and services provided by consumers for consumers emerged and proved a beneficial complement.Conclusion: The consumer-driven products and services provided via the Internet are a potentially important and beneficial complement of traditional health services. They affect the health consumer-provider roles and require changes in healthcare practices.
Keywords: Evidence-based medicine; consumer participation; health promotion; Canada; Internet